Helicobacter pylori Colonization Drives Urokinase Receptor (uPAR) Expression in Murine Gastric Epithelium During Early Pathogenesis - Alpízar Alpízar, Warner (2020)
(1) Background: Persistent Helicobacter pylori infection is the most important risk factor for gastric cancer. The urokinase receptor (uPAR) is upregulated in lesions harboring cancer invasion and inflammation. Circumstantial evidence tends to correlate H. pylori colonization with increased uPAR expression in the human gastric epithelium, but a direct causative link has not yet been established in vivo; (2) Methods: In a mouse model of H. pylori-induced gastritis, we investigated the temporal emergence of uPAR protein expression in the gastric mucosa in response to H. pylori (SS1 strain) infection; (3) Results: We observed intense uPAR immunoreactivity in foveolar epithelial cells of the gastric corpus due to de novo synthesis, compared to non-infected animals. This uPAR induction represents a very early response, but it increases progressively over time as do infiltrating immune cells. Eradication of H. pylori infection by antimicrobial therapy causes a regression of uPAR expression to its physiological baseline levels. Suppression of the inflammatory response by prostaglandin E2 treatment attenuates uPAR expression. Notwithstanding this relationship, H. pylori does induce uPAR expression in vitro in co-cultures with gastric cancer cell lines; (4) Conclusions: We showed that persistent H. pylori colonization is a necessary event for the emergence of a relatively high uPAR protein expression in murine gastric epithelial cells.